Characterization of the chemical composition of extracted oil palm frond (OPF) fibres using TAPPI standard methods and Wise’s method - Razak, Nur Ain; Akhbar, Suffiyana; Mohd Alauddin, Sakinah (Universiti Teknologi MARA Shah Alam, 2025)
Malaysia is the second largest exporter of oil palm, with over 5 million hectares of plantations that produce a large amount of waste materials like palm oil mill waste, empty fruit bunches, fronds, trunks, shells and fibres. Extracting cellulose fibres (CFs) from oil palm fronds (OPF) waste is a smart strategy in managing oil palm plantation waste. Therefore, this study was aimed to extract OPF fibres and determine the actual percentage weight content of the cellulose, hemicellulose and lignin from the extracted OPF fibres. The first part of the study is to extract OPF fibres from Malaysia OPF using direct chemical method. A mixture of 3.2 mol/L nitric acid and 60 mmol/g hydrogen peroxide was used to break down the complex structure of OPF at temperature of 50°C for 48 h. Meanwhile, in the second part of the study, the percentage weight of the lignin, hemicellulose and cellulose in the extracted OPF were determined using the TAPPI 222, Wise’s Method and TAPPI 203 respectively. Additionally, Fourier Transform Infrared Spectroscopy (FTIR) analysis was conducted to characterize and identify the functional groups present in the extracted OPF fibres. The yield of successful extracted OPF fibres using direct chemical treatment is 51.3 ± 0.7%. Meanwhile, the analysis result shows that the extracted OPF fibres contained 7 ± 0.5 wt% of lignin, 32 ± 4.1 wt% of hemicellulose and 37 ± 4.5 wt% of cellulose. The actual content of lignin, hemicellulose and cellulose in the extracted OPF fibres is useful to guide for suitable commercial sustainable applications based on the required strength.